Evaluating progress of European vocational education and training systems : indicators in education - Lauterbach, Uwe [Verfasser] (My University, 2008)
"The quality of an education system or a comparative international assessment refers more and more to quantitative parameters, i.e. 'educational indicators'. The paper aims to analyse the structure of several educational indicators and indicator systems and answer the question 'What can educational indicators achieve?' Starting with a general consideration of the term "indicator" the findings are applied to the educational area and the development of educational indicators is analysed critically. Beginning in the 1950s, following the empirical turn in research methods, and the growing significance of approaches from economics of education, indicators are now applied in national and international settings. The findings show that the combination of the quantitative and qualitative approach is more successful as the isolated research." (Autorenreferat, BIBB-Doku)
Keywords: L 6 Qualität; I 2.2 Europa; Berufsbildungssystem; Europäischer Bildungsraum; Bewertung; Leistungsfähigkeit; Qualität; Indikatoren; Europa